How do Test Scores at the Ceiling Affect Value-Added Estimates?. Issue 1 (1st January 2018) - Resch, Alexandra; Isenberg, Eric
ABSTRACT: Some educators are concerned that students with test scores at top of the test score distribution will negatively affect the value-added estimates of teachers of those students. A conventional wisdom has sprung up suggesting that students with very high test scores have "no room to grow, " so value-added estimates for teachers with high-performing students will be depressed even for highly effective teachers. Using empirical data, we show that under normal circumstances, in which few students score at the ceiling, a teacher of high-performing students—even with many students scoring at the ceiling on the pre-test—can have a high value-added estimate. To understand how more extreme ceiling effects can change value-added estimates, we simulate a low ceiling, causing student test achievement data of high-scoring students to become less precise when a single score represents a large range of possible achievement. We find that the problem of test score ceilings for an evaluation system is not that it pushes the value added of every teacher of high-achieving students toward the bottom of the distribution of teachers, but rather shrinks it toward the middle.